ESG disclosure facilitator: How do the multiple large shareholders affect firms’ ESG disclosure? evidence from China - Wang, Liang; Fan, Xuchang; Zhuang, Hongyu (Frontiers in Environmental Science, 2023)
The Environmental, social, and governance (ESG) disclosure is an important aspect of firms’ strategies. Therefore, exploring how to facilitate the firms’ ESG disclosure is necessary. This paper examines the role of multiple large shareholders (MLS, hereafter) in facilitating a firm’s ESG disclosure. Using a sample of Chinese listed firms during 2011-2020, we compare the ESG disclosure of firms having MLS with that of firms having a single large shareholder (SLS, hereafter) and find that having MLS associated with significantly higher ESG disclosure. After addressing endogeneity and altering the measurement of MLS, the benchmark results still hold after. Additional analysis shows that MLS exerts a more prominent positive effect on ESG disclosure in SOEs. We also examine the role of the other large shareholders in facilitating firms’ ESG disclosure. Our findings reveal a bright side of MLS: it facilitates ESG disclosure by monitoring. Therefore, this paper’s conclusion sheds new light on the bright side of MLS from the perspective of firms’ ESG disclosure and provides insights into how to improve ESG disclosure.